Meningkatkan Kompetensi Pedagogik Guru Di Sekolah Dasar Melalui Pengawasan Yang Dilakukan Oleh Kepala Sekolah. - feby kurniawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
ABSTRACT The purpose of this research is to clarify how school administrators supervise teachers to improve pedagogical skills in the classroom. This study focuses on two issues: (1) how to improve school education by involving the community, and (2) the biggest challenges in content management and teacher development. Data mining and constructive methods were used in this investigation. The results showed that effective methods for managing principals and training teachers consisted of: (1) routine classroom practices, (2) supervision by administrators and educators, (3) floating procedures for describing class visits, and (4) evaluation of leadership activities with the intention of discussing and sharing ideas to improve teaching in the classroom. However, there are also constraints on the capacity of principals to supervise school administrators, including (1) Management issues, such as control of school administrators, teacher anxiety, and educators' lack of understanding of supervision; and (2) The decisions made by the school administration, such as the implementation of action plans, curriculum, teaching resources, teaching strategies, and teaching methods used by teachers in the teaching staff. Due to their busy schedule outside of school hours and the lack of support and incentives for teachers, especially in terms of preparing them for monitoring, the follow-up of school administrators was inadequate. Principals, teacher pedagogic competence, and monitoring are the keywords. Keywords: supervision, school principals, and teacher pedagogic competence